2016
DOI: 10.1038/ncomms11697
|View full text |Cite
|
Sign up to set email alerts
|

BK channels in microglia are required for morphine-induced hyperalgesia

Abstract: Although morphine is a gold standard medication, long-term opioid use is associated with serious side effects, such as morphine-induced hyperalgesia (MIH) and anti-nociceptive tolerance. Microglia-to-neuron signalling is critically involved in pain hypersensitivity. However, molecules that control microglial cellular state under chronic morphine treatment remain unknown. Here we show that the microglia-specific subtype of Ca2+-activated K+ (BK) channel is responsible for generation of MIH and anti-nociceptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 68 publications
1
67
0
Order By: Relevance
“…Nevertheless, since the abrupt discontinuation of prolonged opioid use can result in a withdrawal syndrome, including enhanced pain, the OIH may in fact represent the opioid withdrawal-induced hyperalgesia [reviewed by (134)]. The majority of studies have focused on the effects of morphine and on MOP receptors, but only a few directly addressed the microglia following chronic morphine treatment, and showed that tolerance and/or OIH were reduced by microglia depletion (105,135) (Figure 1C). The former study proposed that morphine activated MOP receptors on spinal cord microglia to increase the expression of purinergic P2X4 receptors, which triggered the (MOP receptor-independent) release of brainderived neurotrophic factor (BDNF) from microglia.…”
Section: Gliamentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, since the abrupt discontinuation of prolonged opioid use can result in a withdrawal syndrome, including enhanced pain, the OIH may in fact represent the opioid withdrawal-induced hyperalgesia [reviewed by (134)]. The majority of studies have focused on the effects of morphine and on MOP receptors, but only a few directly addressed the microglia following chronic morphine treatment, and showed that tolerance and/or OIH were reduced by microglia depletion (105,135) (Figure 1C). The former study proposed that morphine activated MOP receptors on spinal cord microglia to increase the expression of purinergic P2X4 receptors, which triggered the (MOP receptor-independent) release of brainderived neurotrophic factor (BDNF) from microglia.…”
Section: Gliamentioning
confidence: 99%
“…These actions were implied to mediate OIH, but not tolerance (105). Hayashi et al (135) suggested that both tolerance and OIH involved microglia MOP receptor-induced secretion of arachidonic acid (AA) and subsequent activation of microglial large conductance Ca 2+ -activated K + (BK) channels in the spinal cord. Several other studies showed the correlation between tolerance or OIH and the involvement of spinal cord microglia and/or astrocytes in morphine-treated animals.…”
Section: Gliamentioning
confidence: 99%
“…For example, the density of Iba-1positive microglia in cortex and striatum are reduced after subchronic opioid treatment but increased again after spontaneous withdrawal 11 . Neuroinflammation also has a complex role in pain and tolerance to opioid analgesics and microglia have been recently identified as playing a key role in the paradoxical development of opioid-induced hyperalgesia, 12,13 although there are likely multiple other mechanisms involved. Morphine potentiates lipopolysaccharide-induced microglia activation via both opioid receptor mediated and TLR4-mediated pathways 14 .…”
Section: Opioid Abuse Has Reached Epidemic Proportions In the Unitedmentioning
confidence: 99%
“…Changes in the activity of BK Ca channels in microglia have been demonstrated to be associated with morphine‐induced hyperalgesia (Hayashi et al, ). As reported previously (Chen et al, ), the activity of BK Ca channels was detected in mHippoE‐14 neurons.…”
Section: Discussionmentioning
confidence: 99%